Design of a risk assessment methodology for the introduction of invasive species from ship ballast waters: The case of Arzew port" - A BOUDA; N BACHARI; L BAHMED; R BOUBENIA (Management of Environmental Quality, 2016)
Purpose – Ballast water of merchant ship is a source of introduction of invasive species around the globe. The purpose of this paper is to present a quantitative risk assessment applied to a model port, the Port of Arzew in Algeria, and based on an analysis of this port’s shipping traffic. Design/methodology/approach – The risk assessment for introduction of invasive species is interpreted in the form of a probabilistic process, with a combination of two probabilities. The first probability is related to the ability of a species to arrive to the destination (recipient port), depending on the quantity of water ballast discharged and the duration of voyage. The second one is based on the species ability to survive in their new environment, which depends on the environmental similarity between donor port and Arzew port. Findings – This assessment’s outcome consists on a classification of scenarios regarding their acceptability. Consequently, it helped to classify donor ports according to a risk scale, from low risk to high-risk donor ports. Research limitations/implications – The phenomenon of invasion of aquatic species is a complex process. Factors such as adaptation and tolerance of species, the attendance or absence of predators, were not taken into account in this study. Practical implications – This study could be used by the maritime administration as a decision-making tool regarding the issue of exemptions under the IMO International Convention on the Management of Ballast Water and Sediments 2004. Originality/value – This is one of the first known studies in Algeria and dealing with ballast water management. The results of this assessment provide useful information to policy makers, in order to develop a national strategy to reduce the impact of shipping pollution on the marine environment.